Statistical reporting in randomized controlled trials from the dermatology literature: a review of 44 dermatology journals. (1st July 2015) - McClean, M.; Silverberg, J.I.
Summary: Background: The validity of randomized controlled trials (RCTs) is determined by several statistical factors. Objectives: To determine the level of recent statistical reporting in RCTs from the dermatology literature. Methods: We searched MEDLINE for all RCTs published between 1 May 2013 and 1 May 2014 in 44 dermatology journals. Results: Two hundred and ten articles were screened, of which 181 RCTs from 27 journals were reviewed. Primary study outcomes were met in 122 (67·4%) studies. Sample size calculations and beta values were reported in 52 (28·7%) and 48 (26·5%) studies, respectively, and nonsignificant findings were supported in only 31 (17·1%). Alpha values were reported in 131 (72·4%) of studies with 45 (24·9%) having two‐sided P ‐values, although adjustment for multiple statistical tests was performed in only 16 (9·9% of studies with ≥ two statistical tests performed). Sample size calculations were performed based on a single outcome in 44 (86·3%) and multiple outcomes in six (11·8%) studies. However, among studies that were powered for a single primary outcome, 20 (45·5%) made conclusions based on multiple primary outcomes. Twenty‐one (41·2%) studies relied on secondary/unspecified outcomes. There were no differences for primary outcome being met (Chi‐square, P = 0·29), sample size calculations ( P ≥ 0·55), beta values ( P = 0·89), alpha values ( P = 0·65), correction for multiple statistical testing ( P = 0·59), two‐sided alpha ( P = 0·64), support of nonsignificant findings (Fisher's exact, P = 0·23) based on the journal's impact factor. Conclusions: Levels of statistical reporting are low in RCTs from the dermatology literature. Future work is needed to improve these levels of reporting.